Determination of pKa values of fluphenazine analogs by reversed-phase high-performance liquid chromatography - Sobczak Agnieszka; Beata Kaźmierska; Piotr Świątek; Izabela Muszalska-Kolos (Polskie Towarzystwo Farmaceutyczne, 2023)
Phenothiazine and its derivatives exhibit many properties. Hence they are the starting structures for many new potential drugs, biologically active compounds, dyes, etc. In this paper, we investigated a series of five fluphenazine analogs synthesized exhibiting inhibition of multidrug resistance (MDR) in tumor cells. During the drug discovery process, the determination of physicochemical properties of new compounds, such as dissociation constant values (pKa), is essential because it directly affects their pharmacokinetic profile. Thus, this study aimed to determine the pKa values of fluphenazine and its derivatives from the mobile phase pH dependence of the retention factor with the reverse phase liquid chromatographic method. Binary mixtures of phosphate buffer (pH 2.3-11.5) and acetonitrile (40-55%) in different percentages and the Gemini NX C18 column as the stationary phase were used in the tests. The pKa' values of fluphenazine derivatives at experimental concentrations of organic solvent were determined based on the obtained sigmoidal k curves as a function of pH. Then these values were extrapolated to 0% acetonitrile to obtain the actual pKa values. Moreover, a comparative evaluation of chromatographically obtained and computationally calculated pKa parameters was carried out.